2018
DOI: 10.1088/1361-6595/aacd70
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modeling of plasmas for gaseous plasmonics

Abstract: The electromagnetic response of a resonant cavity in the presence of plasma discharges is studied, and a model to predict the formation of microwave pulses is developed using fluid plasma simulations and analytic microwave theory. Results for a 14 GHz rectangular cavity partially filled with plasma are then presented from both the model and from experiment as validation. Experimental results are shown to have good agreement with predicted values. It is seen that microwave pulses are generated with widths and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The plasma ignition causes the transmission to drop 20 dB within 1 µs then recover within 75 µs. Compared to our previous work using a simple two copper post resonator in a WR62 waveguide [12], the initial transmission drop occurs in approximately the same time due to a similar voltage pulse waveform, while the recovery is faster by a factor of 5 due to the higher pressure (10 Torr versus 2 Torr). However, it should not be concluded that the WR62 resonator experiments should also be ran at 10 Torr, as such an increase in the pressure would result in a excessively high electron collision frequency, and hence increase in losses within the cavity.…”
Section: Low Microwave Power Experimentsmentioning
confidence: 52%
See 4 more Smart Citations
“…The plasma ignition causes the transmission to drop 20 dB within 1 µs then recover within 75 µs. Compared to our previous work using a simple two copper post resonator in a WR62 waveguide [12], the initial transmission drop occurs in approximately the same time due to a similar voltage pulse waveform, while the recovery is faster by a factor of 5 due to the higher pressure (10 Torr versus 2 Torr). However, it should not be concluded that the WR62 resonator experiments should also be ran at 10 Torr, as such an increase in the pressure would result in a excessively high electron collision frequency, and hence increase in losses within the cavity.…”
Section: Low Microwave Power Experimentsmentioning
confidence: 52%
“…The lowpower microwave pulse data from figure 5 can be also used as a diagnostic of the plasma density resident inside the microwave cavity. There are several ways to do this including electromagnetic simulations [7,11] and analytic methods [12,15,16], with the latter being sufficient for most estimation purposes. We have previously described a theory of plasma density estimation [12], and for convenience to the reader, we repeat the equation for the nondimensional frequency shift ∆ω res = (ω res − ω 0 )/ω 0 , where the subscript 0 denotes the unperturbed properties,…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations